2022
DOI: 10.3390/foods11182899
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analyses Providing Insights into the Coloring Mechanism of Docynia delavayi

Abstract: The metabolome and transcriptome profiles of three different variations of mature Docynia delavayi fruit were synthesized to reveal their fruit color formation mechanism. A total of 787 secondary metabolites containing 149 flavonoid metabolites, most of which were flavonoids and flavonols, were identified in the three variations using ultra performance liquid chromatography- tandem mass spectrometry (UPLC-MS/MS), and we found that the secondary metabolites cyanidin-3-O-galactoside and cyanidin-3-O-glucoside we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Structural genes directly encode enzymes required in the anthocyanin biosynthetic pathway, such as Phenylalanine ammonia lyase, Chalcone synthase, Chalcone isomerase, Flavanone 3-hydroxylase, Flavonoid 3’- hydroxylase, Dihydroflavonol-4-reductase, Leucoanthocyanidin dioxygenase, Anthocyanidin 3-O-glucosyltransferase, etc ( Li et al., 2020 ; Liu et al., 2021 ; Kaur et al., 2022 ). Through transcriptome sequencing, researchers found that anthocyanin biosynthesis is mainly regulated by structural genes CHS, CHI, F3H, DFR, LODX and GST, among which CHS is an early biosynthesis gene of anthocyanin ( Wang et al., 2022 ). 72% of the structural genes regulating anthocyanin synthesis were up-regulated, and most of the differentially expressed genes had the highest expression level at 34 day after pollution, when the ratio of anthocyanin content to fresh weight was also the highest ( Ming et al., 2021 ).…”
Section: Synthesis Mechanismmentioning
confidence: 99%
“…Structural genes directly encode enzymes required in the anthocyanin biosynthetic pathway, such as Phenylalanine ammonia lyase, Chalcone synthase, Chalcone isomerase, Flavanone 3-hydroxylase, Flavonoid 3’- hydroxylase, Dihydroflavonol-4-reductase, Leucoanthocyanidin dioxygenase, Anthocyanidin 3-O-glucosyltransferase, etc ( Li et al., 2020 ; Liu et al., 2021 ; Kaur et al., 2022 ). Through transcriptome sequencing, researchers found that anthocyanin biosynthesis is mainly regulated by structural genes CHS, CHI, F3H, DFR, LODX and GST, among which CHS is an early biosynthesis gene of anthocyanin ( Wang et al., 2022 ). 72% of the structural genes regulating anthocyanin synthesis were up-regulated, and most of the differentially expressed genes had the highest expression level at 34 day after pollution, when the ratio of anthocyanin content to fresh weight was also the highest ( Ming et al., 2021 ).…”
Section: Synthesis Mechanismmentioning
confidence: 99%
“…The gene function was annotated via the GO and KEGG database. The quantification of transcript abundance and identification of differential expression genes (DEGs) were referred to the previous researches (Wang et al, 2022b; Xia et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, its fruit are rich in flavonoid bioactive substances, which play effective roles in anti-tumor and hypoglycemic (Deng et al, 2014; Wang et al, 2023a). To increase the efficiency of conservation and utilization of D. delavayi germplasm resource, its genetic diversity, plus-tree selection, mechanism of pericarp color variation, metabolome in leaves and fruit were studied in recent years (Chen et al, 2022; Li et al, 2022a; Peng et al, 2021; Wang et al, 2023b; Wang et al, 2022b; Xia et al, 2022; Xu et al, 2023). However, the lack of genome-wide information considerably limits the conduct of its molecular breeding efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus transcription factor activity and structural gene control are essential for the expression of anthocyanins. PAL, C4H, 4CL, CHS, CHI, DFR, LDOX, ANS and UFGT were among the structural genes ( Wang et al., 2022 ). The transcription-related variables MYBs, MYCs, bZIPs, B-box, MYBbHLH-WD40 (MBW) complex, NACs, and WRKYs are important regulators of anthocyanin biosynthesis induction ( Sun et al., 2022 ).…”
Section: Anthocyanin Metabolismsmentioning
confidence: 99%